ISLAMIC PARENTING di WILAYAH MINORITAS (Cara Keluarga Muslim Menanamkan dan Mempertahankan Keyakinan Anggota Keluarga di Daerah Semarapura Tengah, Klungkung – Bali) (Jurnal Bimbingan dan Konseling Islam, 2016)
Islamic Parenting in minority region ( The way of Islamic family to teach and maintain in the member of the family in the center of Semarapura Tengah, Klungkung – Bali). There two focuses in this research (1) How the way the process of to Islamic Parenting in minority region ( The way of Islamic family to teach and maintain in the member of the family in the center of Semarapura Tengah, Klungkung – Bali)? (2) How the result of Islamic Parenting in minority region ( The way of Islamic family to teach and maintain in the member of the family in the center of Semarapura Tengah, Klungkung – Bali)? The researcher uses qualitative descriptive method to answers the research problem in the following above. The aim of this method is to express the faith of the member in minority region. The data that use in this research derived from observation and documentation that serving in chapter presentation and analyzing data. Subject of this research was derived from the Muslim family in center of Semarapura Tengah, Klungkung – Bali. The previous step is analyzing data that already found and collected to answer the research problem. The process of Islamic Parenting in minority region, the parents not only give advice and surveillance but also show good behavior as the role modal for their children. The parents also teach moral value of Islam and also strength relationship and harmonization. The results of the process Islamic Parenting in minority region are application of the parents to obey the rule of the God that become moral value of islam that teach start from childhood also in their society as a harmony life without any differences from the race, region  or religion, and etc.